Perú: unauthorized use of third party´s trademarks on “Google ads” A trademark infringement or an act of unfair competition? - Sosa, Alex (2020)
In the current online advertising market, economic operators seek to divert demand of consumers to their offers through programmatic advertising. One of the most persuasive and effective is Google Ads. In this article, we shall analyse whether the unauthorized use of third-party trademarks as keywords on “Google Ads” constitute an act of unfair competition or a trademark infringement.